The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/jcla.22862
|View full text |Cite
|
Sign up to set email alerts
|

The clinical value of hematological markers in rheumatoid arthritis patients treated with tocilizumab

Abstract: BackgroundEmerging evidence indicates that some hematological markers have critical value in evaluating treatment response. This study was performed to determine the clinical value of hemoglobin (Hb), platelet (Plt), neutrophil‐to‐lymphocyte ratio (NLR), and platelet‐to‐lymphocyte ratio (PLR) in rheumatoid arthritis (RA) patients treated with tocilizumab (TCZ).MethodsFifty‐two RA patients receiving TCZ were recruited and followed for 6 months. The values of abovementioned hematological markers were collected. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 43 publications
0
5
0
1
Order By: Relevance
“…In addition, PBMC hsa_circ_0000175 was correlated with inflammatory markers, including WBc, N, N%, L, L% and NLR, which reflect the activity and severity of RA (28). Moreover, PBMC hsa_circ_0008410 was correlated with TJc, disease duration and PLT, which are associated with the development of peripheral neuropathy and are correlated with dAS28 (29,30), and PcT, which is associated with the treatment of RA (31). Thus, these data indicated that PBMc hsa_circ_0000175 and hsa_ circ_0008410 were associated with the activity and severity of RA.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, PBMC hsa_circ_0000175 was correlated with inflammatory markers, including WBc, N, N%, L, L% and NLR, which reflect the activity and severity of RA (28). Moreover, PBMC hsa_circ_0008410 was correlated with TJc, disease duration and PLT, which are associated with the development of peripheral neuropathy and are correlated with dAS28 (29,30), and PcT, which is associated with the treatment of RA (31). Thus, these data indicated that PBMc hsa_circ_0000175 and hsa_ circ_0008410 were associated with the activity and severity of RA.…”
Section: Discussionmentioning
confidence: 98%
“…In a more recent trial with 118 included patients, 92% of treated NMOSD patients were relapse-free after 48 weeks compared to 69% in the azathioprine group with similar findings regarding disability progression [ 233 ]. Neither did treatment alter lymphocyte, B cell, transitional B cell and plasmablast count, nor did it alter BAFF levels of treated patients [ 234 , 235 ]. However, Toclizumab was shown to reduce memory B cell subsets in rheumatoid arthritis patients as well as IgA and IgG serum levels [ 236 ].…”
Section: Novel and Future Nmosd Treatmentsmentioning
confidence: 99%
“…Treatment with tocilizumab had neither an impact on total lymphocyte count and absolute B cell, transitional B cell and plasmablast numbers, nor did it alter BAFF levels of treated patients [ 156 , 157 ]. However, tocilizumab was shown to reduce memory B cell subsets as well as IgA and IgG serum levels in rheumatoid arthritis patients [ 158 ].…”
Section: Current and Evolving Therapeutic Strategies In Nmosdmentioning
confidence: 99%